Transmarias: direito; direitos e gênero nos embates e enredamentos discursivos sobre a vitimação trans na lei Maria da Penha - Sousa, Tuanny Soeiro (2022)
The adequacy of the Maria da Penha Law (No. 11.340/2006) in cases of domestic and family violence against trans women and travestis has produced a plethora of discourses. This work aims to investigate the discursive clashes which emerge from this subject in order to elicit the simultaneous process of coproduction of “State/Law” and “Gender” that are implied in these systems of meaning. To that end, this research combines methodological and theoretical elements of the “ethnography of papers” with those from the “ethnography of the cyberspace”, while adopting Ernesto Laclau and Chantal Mouffe’s Theory of the Discourse as a method of analysis. The results point to the existence of two forms of discursive formations, which I define “associative” and “antagonizing”. The first, thoroughly distributed throughout the country, mediates and gets mediated by a network of agents belonging to various distinct institutions and social movements who defend the possibility of applying the Maria da Penha Law in the cases mentioned. The second manifests itself only inside the interpretative community, and advocates for the inadequacy of the Maria da Penha Law in those cases. The conclusion is that the dynamics of signification occur through social relations of gender, race and class, and even if they form the present conditions for the recognition of transexual rights, especially because of the ideals of “State/Law” which are intimately tied to the protection of “minorities” and “the vulnerable” or the assurance of “human dignity”, these very conditions ultimately set the stage for the recognition (or lack thereof) of the status of victim in these case of violence.